The acute respiratory distress syndrome: pathophysiology, current clinical practice, and emerging therapies. (2nd December 2018) - Derwall, Matthias; Martin, Lukas; Rossaint, Rolf
ABSTRACT: Introduction : More than fifty years after the first description of acute respiratory distress syndrome (ARDS) by Ashbaugh and colleagues, no specific treatment of the underlying pathophysiological processes is available. The current therapeutic regime is comprised of supportive measures such as lung protective ventilation, restrictive fluid management, paralyzing drugs, and prone positioning. Although vast improvements have been made in ARDS-treatment during the last five decades, mortality among patients with severe ARDS remains at an unacceptable rate of 45%. Areas covered : This article reviews the evolution of the currently used definition, established pathophysiological mechanism, highlights the current best clinical practice to treat ARDS, gives a brief outlook on cutting edge trends in ARDS research and closes with an expert opinion on the subject. Expert commentary : Individualizing the provided measures to specific genotypes is the key challenge in ARDS research today. The ongoing digital revolution will help to individualize ARDS-treatment and will therefore presumably improve survival and quality of life.